Dynamic characteristic difference of steel-spring floating slab track between single-carriage and multi-carriage models. (June 2021) - Chang, Wenhao; Cai, Xiaopei; Wang, Qihao
The steel-spring floating slab track (SSFST) is a low-stiffness structure, sensitive to the vehicle loads. Due to the coupling effect of the superposition of adjacent bogies, it is difficult for conventional single-carriage models to meet the simulation requirements. To find a balance between computation efficiency and authenticity of analytical model results, the influence of carriage number on SSFST should be studied. Based on the finite element method and multi-body dynamics, a refined three-dimensional coupled model of multi-carriage-SSFST-tunnel was established. The difference in the dynamic response of the SSFST between single-carriage and multi-carriage models was analyzed and compared with the measured data. The field test results show that structural displacements and accelerations under the two-carriage model are much closer to the measured data. The dynamic model analysis results show that the maximum displacement of the rail and SSFST in the midspan of the slab increase by 0.48 mm and 0.34 mm under the multi-carriage model, and the vibration reduction effectiveness increases by 1.4–2.0 dB. Dynamic responses of the rail and SSFST show minor differences under the two-carriage and three-carriage models. The article is expected to provide a reference for the theoretical research, design, and layout optimization of subway SSFST.